1979
DOI: 10.1111/j.1365-2125.1979.tb01044.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of enzyme induction on diazepam metabolism in man.

Abstract: 1 The elimination and metabolism of diazepam in man was investigated following the induction of the liver microsomal enzyme system by antipyrine. 2 Seven healthy volunteers were given 1200 mg antipyrine as an inducing agent for a period of 14 days. Before and after the induction period the elimination of diazepam and desmethyldiazepam was measured in the plasma by gaschromatography. As parameters of liver microsomal enzyme activity, antipyrine elimination and gamma‐glutamyl‐ transpeptidase in the plasma, D‐glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Pharmacokinetic studies have shown that the diazepam metabolite, n-desmethyldiazepam, has a elimination half life of about 139 hours, versus 58 hours for the antipyrene related hepatic microsomal enzyme induction rate; 15 animal studies show that it accumulates to a high degree within central white matter regions, 16 and does not efflux very readily relative to diazepam. It is therefore hypothesized that prolonged retention of diazepam metabolites may play an additional role in the pathogenesis of diazepam related DPHLE, with accumulation of this metabolite likely occurring within central white matter.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic studies have shown that the diazepam metabolite, n-desmethyldiazepam, has a elimination half life of about 139 hours, versus 58 hours for the antipyrene related hepatic microsomal enzyme induction rate; 15 animal studies show that it accumulates to a high degree within central white matter regions, 16 and does not efflux very readily relative to diazepam. It is therefore hypothesized that prolonged retention of diazepam metabolites may play an additional role in the pathogenesis of diazepam related DPHLE, with accumulation of this metabolite likely occurring within central white matter.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic clearance of diazepam is enhanced by concurrent treatment with antipyrine (Ohnhaus et al, 1979) and rifampicin (Ochs et al, 1981). Dichloralphenazone (Riddell et aI., 1980) and clozapine (Ryan and Matthews, 1970) have been reported to stimulate the metabolism of phenytoin.…”
Section: Other Drugsmentioning
confidence: 98%